The two eyes of the Earth : art and ritual of kingship between Rome and Sasanian Iran - Canepa, Matthew P., 1975- (University of California Press, 2009)
This pioneering study examines a pivotal period in the history of Europe and the Near East. Spanning the ancient and medieval worlds, it investigates the shared ideal of sacred kingship that emerged in the late Roman and Persian empires. This shared ideal, while often generating conflict during the four centuries of the empires' coexistence (224-642), also drove exchange, especially the means and methods Roman and Persian sovereigns used to project their notions of universal rule: elaborate systems of ritual and their cultures' visual, architectural, and urban environments. Matthew Canepa expl.
Keywords: Rome -- Relations -- Iran.; Iran -- Relations -- Rome.; Rome -- Kings and rulers.; Iran -- Kings and rulers.; Monarchy -- Social aspects -- Rome.; Monarchy -- Social aspects -- Iran.; Rites and ceremonies -- Rome.; Rites and ceremonies -- Iran.; Romans -- Social life and customs.; Sassanids -- Social life and customs.; Rites et cérémonies -- Rome.; Rites et cérémonies -- Iran.; Romains -- Mœurs et coutumes.; Sassanides -- Mœurs et coutumes.; POLITICAL SCIENCE -- Globalization.; HISTORY -- Ancient -- General.; International relations; Kings and rulers; Manners and customs; Monarchy -- Social aspects; Rites and ceremonies; Romans -- Social life and customs; Iran; Rome (Empire); Koningschap.; Apotheose (godsdienst); Symboliek.; Uitwisseling.; Iran.; Romeinse rijk.; ancient history.; ancient rome.; ancient societies.; ancient world.; art.; byzantium.; china.; classical heritage.; classical history.; court life.; engaging.; europe.; global politics.; global powers.; historical.; iranian history.; islam.; kingship.; medieval europe.; medieval society.; medieval times.; near east.; nonfiction study.; persian empire.; pivotal period.; political history.; roman empire.; rome.; royal intrigue.; royalty.; sacred kingship.; sasanian iran.; south asia.; Electronic book.